How to strengthen basic competencies in self-care – a pre-post interventional study with postgraduate trainees in family medicine in Germany. Issue 5 (4th July 2021) - Schwill, S; Krug, K; Valentini, J; Rentschler, a; Nikendei, C; Szecsenyi, J; Bugaj, TJ
ABSTRACT: Introduction : Self-care includes taking care of our psychosocial health. Many experts agree that self-care should be included in training for Family Medicine (FM) residents, though it is unclear to what extent and by what means. Objective: The aim of this study was to evaluate competencies of FM residents in self-care and changes in knowledge, skills and attitudes after an educational compact intervention. Methods : The authors performed a pre-post comparison on residents who were registered in the FM residency program KWBW VerbundweiterbildungPLUS© (n = 401). FM residents were offered participation in a self-care training (270 minutes featuring a broad spectrum of input and practical experience). The intervention group (IG) completed a questionnaire directly before the seminar (T1) and 10 weeks afterwards (T2). Non-attendees (=control group; CG) were asked to fill out a basic questionnaire once. Basic questionnaires for IG and CG covered previous experiences and skills while the follow-up questionnaire at T2 also focused on change of competencies and attitudes. All questionnaires contained free-text questions to capture qualitative impressions. Results : 287 FM residents (IG: n = 212; CG: n = 75) participated in the study. Generally, 86.4% of FM residents had worried that their profession might endanger their personal health (T1: n = 180, CG: n = 68). At T2, 59.5% of IG (n = 66/111) declared that they would not worry about their personal health anymore (T1:T2, p < .01). IG learned to facilitate time for recreation (T1:T2, p = .04) and to use relaxation techniques (T1:T2, p = .01). Gain in competence was described in awareness of stress, self-reward, activation of personal resources, and time management. A total of 85.6% of IG reflected their attitudes towards psychosocial health of physicians in general (n = 95/111) and 22.5% of IG changed the views on their own health (n = 25/111) in terms of improved risk-awareness, increased intention for self-care and change of behavior. Conclusion : A compact intervention in self-care strengthens competencies, increases awareness, and helps FM residents identify their psychosocial health risks. Further research is necessary to specify the effectiveness of similar compact interventions in self-care and their long-term results.